2017
DOI: 10.1038/srep40024
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of FADS2 transcription by SREBP-1 and PPAR-α influences LC-PUFA biosynthesis in fish

Abstract: The present study was conducted to explore the mechanisms leading to differences among fishes in the ability to biosynthesize long-chain polyunsaturated fatty acids (LC-PUFAs). Replacement of fish oil with vegetable oil caused varied degrees of increase in 18-carbon fatty acid content and decrease in n-3 LC-PUFA content in the muscle and liver of rainbow trout (Oncorhynchus mykiss), Japanese seabass (Lateolabrax japonicus) and large yellow croaker (Larimichthys crocea), suggesting that these fishes have differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 62 publications
7
62
1
Order By: Relevance
“…Recent studies have shown that HUFAs decrease fat accumulation and affect the activities and gene expression of lipolysis‐related enzymes, such as LPL, which hydrolyses TG of circulating chylomicrons and very low‐density lipoproteins (VLDLs). The transcription factor PPARs play key roles in the catabolism and storage of fatty acids (Kjӕr, Todorčević, Torstensen, Vegusdal, & Ruyter, ; Viswakarma et al, ), in which PPARα is a vital gene that could increase fatty acid oxidation in adipocytes, and its expression levels could reflect the presence of β‐oxidation (Dong et al, ; Zheng et al, ; Zuo, Ai, Mai, & Xu, ). Together with LPL, HL is responsible for the clearance of TG from the circulation (Yang & Subbaiah, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that HUFAs decrease fat accumulation and affect the activities and gene expression of lipolysis‐related enzymes, such as LPL, which hydrolyses TG of circulating chylomicrons and very low‐density lipoproteins (VLDLs). The transcription factor PPARs play key roles in the catabolism and storage of fatty acids (Kjӕr, Todorčević, Torstensen, Vegusdal, & Ruyter, ; Viswakarma et al, ), in which PPARα is a vital gene that could increase fatty acid oxidation in adipocytes, and its expression levels could reflect the presence of β‐oxidation (Dong et al, ; Zheng et al, ; Zuo, Ai, Mai, & Xu, ). Together with LPL, HL is responsible for the clearance of TG from the circulation (Yang & Subbaiah, ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a study in mice showed that perinatal manipulation of ALA intake alters Fads2 promoter methylation in offspring livers [64], whereas we showed that the activity of the fish fads2 promoter under our experimental conditions would be more affected by the activity/availability of TFs. Certainly, the regulatory effects of SREBP-1 and PPAR-α in response to dietary fatty acids are quite different in rainbow trout (freshwater), Japanese sea bass (euryhaline) and yellow croaker (marine), which may contribute to the differential LC-PUFA biosynthesis abilities (via fads2 regulation) among fish that have adapted to different ambient salinity [22], and act in concert to other differences such as the presence of a SP1 site in the promoter of freshwater species that is absent in marine fish [23]. Likewise, the nutritional condition of European sea bass larvae with high-or low-PUFA diets did not change the methylation level of 28 CpG sites examined within the fads2 promoter [25].…”
Section: Constrains To Program Fish Fads2mentioning
confidence: 99%
“…The high replacement of marine feed ingredients by alternative raw materials is, thereby, a complex issue, and the total or high replacement of FO by vegetal oils (VO) can compromise fish health [14] and the nutritive value of fish meat [15,16]. This risk assessment is especially relevant in marine farmed fish, since they have a limited ability to convert α-linolenic acid (ALA, 18:3n-3) into eicosapentaenoic acid (EPA, 20:5n-3) and docosahexaenoic acid (DHA, 22:6n-3) [17]. Fatty acid desaturase 2 (Fads2) catalyzes the first and rate limiting step in this pathway and its regulation and activity has been studied in a wide-range of marine (gilthead sea bream [18], black sea bream [19], European sea bass [20], Japanese sea bass [21], large yellow croaker [22], orange-spotted grouper [23]) and freshwater (rainbow trout [22], striped snakehead [24]) fish species.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations